Anaerobic power and hydration status in combat sport athletes during body mass reduction - Kurylas, A.; Chycki, J.; Zajac, T. (Baltic Journal of Health and Physical Activity, 2019)
Hydration is one of the most significant issues for combat sports as athletes often use water restriction for quick weight loss before competition. There is significant evidence to indicate that the hypohydration status impairs anaerobic performance. The aim of this study was to investigate if hypohydration, to reach a weight category, affects anaerobic performance.